Glyoxylase-1 combats dicarbonyl stress and right ventricular dysfunction in rodent pulmonary arterial hypertension - Prisco, Sasha Z.; Hartweck, Lynn; Keen, Jennifer L.; Vogel, Neal; Kazmirczak, Felipe; Eklund, Megan; Hemnes, Anna R.; Brittain, Evan L.; Prins, Kurt W. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Evaluate the effects of protein glycation on mitochondrial fatty acid oxidation (FAO) and right ventricular (RV) function. Background: Heightened glycolytic flux is associated with RV dysfunction in pulmonary arterial hypertension (PAH). Methylglyoxal, a glycolysis byproduct, is a highly reactive dicarbonyl that has toxic effects via nonenzymatic post-translational modifications (protein glycation). Methylglyoxal is degraded by the glyoxylase system, which includes the rate-limiting enzyme glyoxylase-1 (GLO1), to protect cells from dicarbonyl stress. However, the consequences of altered dicarbonyl metabolism on RV function are unknown. Methods: Bioinformatics analysis of previously identified glycated proteins predicted how protein glycation regulated cardiac function. Methylglyoxal treatment of H9c2 cardiomyocytes evaluated the consequences of excess protein glycation on mitochondrial respiration. The effects of adeno-associated virus serotype 9-mediated (AAV9) GLO1 expression on RV function in monocrotaline rats were quantified with echocardiography and hemodynamic studies. The relationships between protein glycation, defined by hemoglobin A1C, and RV strain were examined in 38 PAH patients. Results: In silico analyses highlighted multiple mitochondrial metabolic pathways that may be affected by protein glycation. Exogenous methylglyoxal minimally altered mitochondrial respiration when cells metabolized glucose, however methylglyoxal depressed FAO. AAV9-Glo1 increased RV cardiomyocyte GLO1 expression, reduced total protein glycation, partially restored mitochondrial density, and decreased lipid accumulation. AAV9-Glo1 blunted RV hypertrophy/fibrosis and improved RV systolic and diastolic function. Finally, higher levels of hemoglobin A1C were associated with diminished RV strain and heightened RV sensitivity to afterload in PAH patients. Conclusions: Deranged methylglyoxal metabolism and excess protein glycation results in depressed mitochondrial FAO and RV dysfunction.